Information and financial crisis policy-making. Issue 3 (9th March 2017) - Gandrud, Christopher; O'Keeffe, Mícheál
ABSTRACT: The degree to which governments intervene to contain financial crises varies considerably. We aim to understand why policy-makers choose the level of intervention they do to contain financial shocks. In particular, we want to understand why policy-makers may choose policies that create outcomes they do not want. We focus on a defining feature of financial crisis policy-making that has been largely unaddressed in the literature on policy responses to crises: policy-makers lack good information about the health of their banking systems. So they rely on their bureaucrats and other actors for necessary information. However, information providers may have different policy preferences. To understand the interactions between these actors and the implications for policy choice, we advance a signalling game of financial crisis containment. We use a case study of the recent Irish crisis to demonstrate how information asymmetries can have a significant impact on bailout choices.